2018
DOI: 10.12691/ajmr-6-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Antibiotic against Uropathogen Isolated at a Tertiary Care Hospital of Dhaka City

Abstract: Background: The antibiotic sensitivity pattern of uropathogenic bacteria is varied with different frequency. Objective: The purpose of the study was to determine the pattern of antibiotic sensitivity against uropathogens isolated from a tertiary care hospital of Dhaka City. Methodology: A cross-sectional study was conducted in the Department of Microbiology at Shaheed Suhrawardy Medical College, Dhaka, Bangladesh during period of January 2016 to December 2016. Among 307 consecutive urine samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
3
4
0
Order By: Relevance
“…This is in agreement the with study of Khanam et al, who also reported a much lower sensitivity pattern of GNB towards Amoxiclav, azithromycin & cefuroxime. 1 Isolated GNB showed poor sensitivity to Ciprofloxacin (Klebsiella & pseudomonas-44.4%, Enterobacter & Proteus-50%), except E. coli which showed slightly higher sensitivity (64%), which is very much consistent with the findings of Sohely et al 16 E. coli, Klebsiella & proteus showed relatively higher sensitivity to Levofloxacin (70%, 61.1% & 100% respectively) but sensitivity pattern of Enterobacter & Pseudomonas towards Levofloxacin was as low as their sensitivity to ciprofloxacin. This is also true for the study done by Ritu Saha et al 7 & Nahar et al 24 The present study showed that Klebsiella & Proteus had lower sensitivity to nitrofurantoin ( 26 , which is again in agreement with our study.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This is in agreement the with study of Khanam et al, who also reported a much lower sensitivity pattern of GNB towards Amoxiclav, azithromycin & cefuroxime. 1 Isolated GNB showed poor sensitivity to Ciprofloxacin (Klebsiella & pseudomonas-44.4%, Enterobacter & Proteus-50%), except E. coli which showed slightly higher sensitivity (64%), which is very much consistent with the findings of Sohely et al 16 E. coli, Klebsiella & proteus showed relatively higher sensitivity to Levofloxacin (70%, 61.1% & 100% respectively) but sensitivity pattern of Enterobacter & Pseudomonas towards Levofloxacin was as low as their sensitivity to ciprofloxacin. This is also true for the study done by Ritu Saha et al 7 & Nahar et al 24 The present study showed that Klebsiella & Proteus had lower sensitivity to nitrofurantoin ( 26 , which is again in agreement with our study.…”
Section: Discussionsupporting
confidence: 83%
“…A study at a tertiary care hospital in Dhaka, Bangladesh also showed female predominance (58.2%) among culture-positive UTI patients. 1 Ascending infection due to short urethra, the wrong practice of cleaning the perineum forward from the anus to vulva & sexual intercourse may be responsible for this higher frequency of UTI in females. 7 Longer urethra & presence of some natural antimicrobial substances in the prostatic fluid may explain the lower frequency of UTI in the male population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations